Arahan Peningkatan Partisipasi Masyrakat dalam Menjaga Kualitas Lingkungan Permukiman dada Kawasan Cagar Budaya Somba Opu - Surtiah, Minardi; Surya, Batara; Arief, Rimba (Journal of Urban Planning Studies, 2024)
Abstract. The aim of this research is to identify what factors influence the lack of community participation and what are the directions for increasing community participation in the Somba Opu Cultural Heritage Area in maintaining the quality of the residential environment. The method used to find out what factors influence the lack of community participation is multiple regression analysis. Meanwhile, the method used for guidance in increasing community participation in maintaining the quality of the residential environment is qualitative descriptive analysis. The results of this research show that the factors that influence community participation are a sense of security, facilities and infrastructure, respect, knowledge and socialization by the government. From the results of the multiple regression analysis, directions were made from the five influencing factors referring to applicable policies, including the Space Utilization Control Law Number 26 of 2007 Article 1 number 15, Gowa Regency Regional Regulations Number 15 of 2012, and Reserve Site Zoning regulations Somba Opu Culture